Arabic through the Qur'an - Jones, Alan (Cambridge : The Islamic Texts Society, 2005)
Written by a professor of Arabic at Oxford University, this work aims at teaching Arabic using only the vocabulary in the Qur'an. The whole of Arabic grammar is covered in forty lessons. Each lesson is followed by exercises and a key to the exercises is available at the end of the book.
Lesson 1. Nouns and adjectives -- Lesson 2. Plurals -- Lesson 3. The declension of nouns -- Lesson 4. Prepositions -- Lesson 5. The first person singular genitive suffix and the pronoun of separation -- Lesson 6. Demonstratives -- Lesson 7. Idafa -- Lesson 8. The perfect tense -- Lesson 9. Pronominal suffixes -- Lesson 10. The particle ma -- Lesson 11. Kull; ba'd; the accusative of time -- Lesson 12. Kana; qala; lamma -- Lesson 13. The dual -- Lesson 14. Cardinal numbers -- Lesson 15. Derived forms of the verb -- Lesson 16. The imperfect -- Lesson 17. Interrogatives -- Lesson 18. The subjunctive -- Lesson 19. Inna -- Lesson 20. The jussive -- Lesson 21. Laysa; idh; idha; man -- Lesson 22. Verbs with a hamza as one of their radicals -- Lesson 23. Relative sentences -- Lesson 24. Assimilated verbs -- Lesson 25. The elative -- Lesson 26. Doubled verbs -- Lesson 27. Exceptive sentences with illa -- Lesson 28. Hollow verbs -- Lesson 29. The vocative -- Lesson 30. Defective verbs -- Lesson 31. Ordinal and other numbers -- Lesson 32. The imperative -- Lesson 33. The passive -- Lesson 34. More about nouns -- Lesson 35. More on the accusative -- Lesson 36. Conditional sentences -- Lesson 37. More about an;'asa and la'alla -- Lesson 38. Special verbs; law-la -- Lesson 39. The energetic; oaths and exclamations -- Lesson 40. Special uses of ma kana; verbs of wonder, praise and blame.
Keywords: Qur'an -- Language, style; Arabic language -- Grammar